2006
DOI: 10.1080/14786410600899050
|View full text |Cite
|
Sign up to set email alerts
|

A new flavonoid from Chromolaena odorata

Abstract: Fractionation of the aerial parts of Chromolaena odorata afforded a new flavonoid, 5,7-dihydroxy-6,4'-dimethoxyflavanone, in addition to 14 known flavonoid compounds, six of which had not been isolated previously from this plant. The structure of the new compound was determined by spectroscopic methods particularly 2D-NMR analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
0
19
0
1
Order By: Relevance
“…Adetayo et al (2005) reported allelopathic effects of Chromolaena extracts on seed germination and seedling growth of cowpea (Vigna unguiculata), maize (Zea mays), soybean (Glycine max), Chromolaena itself and Tridax procumbens. Several flavonoids have been isolated from the aerial parts of Chromolaena (Pisutthanan et al 2006), and although flavonoids can be allelopathic, all plants produce them and the presence of chemicals is not evidence for allelopathic potential. Allelopathic effects of aqueous and organic extracts of Chromolaena and of its residues in soil have also been reported (Onwugbuta 2001).…”
Section: Traditional Approachmentioning
confidence: 99%
“…Adetayo et al (2005) reported allelopathic effects of Chromolaena extracts on seed germination and seedling growth of cowpea (Vigna unguiculata), maize (Zea mays), soybean (Glycine max), Chromolaena itself and Tridax procumbens. Several flavonoids have been isolated from the aerial parts of Chromolaena (Pisutthanan et al 2006), and although flavonoids can be allelopathic, all plants produce them and the presence of chemicals is not evidence for allelopathic potential. Allelopathic effects of aqueous and organic extracts of Chromolaena and of its residues in soil have also been reported (Onwugbuta 2001).…”
Section: Traditional Approachmentioning
confidence: 99%
“…Skadhauge et al (1997) suggested that barley flavonoids play a role in resistance against Fusarium by several mechanisms such as formation of physical barriers and inhibition of fungal cellulases, pectinases and xylanases. Flavonoids have been reported as a prominent group of phytochemicals from C. odorata (Akinmoladun et al 2007;Ngozi et al 2009;Barua et al 1978;Wollenweber et al 1995;Suksamrarn et al 2004;Pisutthanan et al 2006). Therefore, it could be speculated that a flavonoid or group of different flavonoids present in the leaf extract could be responsible for the reduced B. oryzae infection.…”
Section: Discussionmentioning
confidence: 92%
“…C. odorata is known to contain several bioactive phytochemicals, including quinones, steroids, terpenoids and cardiac glycosides (Akinmoladun et al 2007), cyanogenic glycosides, phytates and saponins (Ngozi et al 2009), alkaloids (Akinmoladun et al 2007;Ngozi et al 2009;Biller et al 1994; Thoden et al 2007), tannins (Akinmoladun et al 2007;Ngozi et al 2009;Apori et al 2000), flavonoids, flavanones and flavones (Akinmoladun et al 2007;Ngozi et al 2009; Barua et al 1978;Wollenweber et al 1995;Suksamrarn et al 2004;Pisutthanan et al 2006), flavonoid glucosides (Wollenweber et al 1995;Hung et al 2011), pyrrolizidine alkaloids (Akinmoladun et al 2007;Ngozi et al 2009;Biller et al 1994; Thoden et al 2007) and essential oils (Koba et al 2011;Kossouoh et al 2011;Joshi 2013). However, whether compounds are active as potential plant-disease control agents remains to be elucidated.…”
mentioning
confidence: 97%
“…It has a wide range of bioactivities such as analgesic, antihelmintic, antiinflammatory, antimalarial, antimicrobial, and antioxidant (Omokhua et al 2016). The chemical constituents of the essential oil include pregeijerene, germacrene D, α-pinene, β-caryophyllene, vestitenone, β-pinene, geijerene, bulnesol, and transocimene (Pisutthanan et al 2006). Dichloromethane extracts of this plant had significant cytotoxic effect against Vero monkey kidney cells (Omokhua et al 2017).…”
Section: Introductionmentioning
confidence: 99%